Effect of Augmented Reality (AR) on Problem Solving Ability in 3D Spatial Modeling in Elementary Schools: Pengaruh Augmented Reality (AR) terhadap Kemampuan Pemecahan Masalah Pada Pemodelan Bangun Ruang 3D di Sekolah Dasar - Untari, Rahmania Sri; Hasanah, Fitria Nur; Wardana, Mahardika Darmawan Kusuma; Andhita, Krisna (Universitas Muhammadiyah Sidoarjo, 2022)
The ability and expertise in solving problems is needed by every student. Augmented Reality (AR) is a learning application that can improve students' skills. This study aims to analyze the effect of problem solving ability in 3D spatial modeling between students before being given AR treatment and before being given AR. This study used a quasi-experimental design. The subjects of the research were 43 students of class V SDN Lakarsantri 2 Surabaya. This study uses test and non-test instruments. The research data were analyzed using paired T-test. The results showed that: 1) there was a significant effect on problem solving between students before being given treatment and before being given AR.